Netter's atlas of human embryology - Cochard, Larry R. 4 0 16; M.D. (Frank Henry), 1906-1991. Netter, Frank H.;Craig, John A.,;Machado, Carlos A. G.; 5 (Teterboro, NJ : Icon Learning Systems, 2002)
A guide to the various stages and complexities of embryonic life and development for humans, featuring over six hundred medical illustrations, focusing on the morphological patterns in the embryo and fetus, and discussing the development of each organ system, the classification of congenital defects, and related topics.
Include index.
Adult;Adult
Keywords: 2 -- 0; 6; Embryology, Human;Embryology -- Atlases.;Atlases.; 20; 2